Perceptions of The Characteristics and Functions of Food Product Packaging in The Light of the COVID-19 Pandemic – Selected Aspects - Wioletta WRÓBLEWSKA; Joanna PAWLAK; Dariusz PASZKO (Communications of International Proceedings, 2021)
Product packaging plays a key role in marketing communication by initiating and establishing contact with consumers. Getting to know customer attitudes and needs, including in terms of food products, is very important, especially now, during the pandemic, which has established new consumption trends, and has effected potentially permanent changes in this respect. The objective of the study was to recognise the opinions of food products buyers on the perception of the characteristics and functions of packaging according to gender while in the COVID-19 pandemic. The results of the research indicate that packaging is an essential part of the product for those surveyed, comprising a set of characteristics and elements co-creating its functions. The surveyed buyers of food products showed more interest in the verbal than the non-verbal elements of packaging. In this time of the COVID-19 pandemic the pragmatic functions of packaging were the most essential for those surveyed, i.e. the informational, protective and practical functions. The environmental and the marketing functions of the packaging were less important. The respondents’ gender almost did not differentiate the perception and order of importance of the respective elements and functions of packaging. Prioritising non-verbal over verbal elements could be due to the specific features of the food products and the epidemic situation, which is inspiring less impulsive, more rational, and better considered shopping decisions.
Keywords: Packaging; Food Product; COVID-19